2021
DOI: 10.1158/1940-6207.capr-20-0609
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Skin Carcinogenesis by the Non-β-blocking R-carvedilol Enantiomer

Abstract: Skin cancer is the most common malignancy worldwide and is rapidly rising in incidence, representing a significant public health challenge. The β-blocker carvedilol has shown promising effects in preventing skin cancer. However, as a potent β-blocker, repurposing carvedilol to an anticancer agent is limited by cardiovascular effects. Carvedilol is a racemic mixture consisting of equimolar S-and R-carvedilol, whereas the R-carvedilol enantiomer does not possess β-blocking activity. Since previous studies sugges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Another study also supported the potential of carvedilol for use in skin cancer prevention 24 . Of note, however, the study also found that carvedilol's non–β‐blocking enantiomer, R‐carvedilol, may be better for treating patients because it has fewer adverse effects than carvedilol.…”
Section: β‐Adrenergic Expression and Signaling In Cancer Cellsmentioning
confidence: 83%
See 1 more Smart Citation
“…Another study also supported the potential of carvedilol for use in skin cancer prevention 24 . Of note, however, the study also found that carvedilol's non–β‐blocking enantiomer, R‐carvedilol, may be better for treating patients because it has fewer adverse effects than carvedilol.…”
Section: β‐Adrenergic Expression and Signaling In Cancer Cellsmentioning
confidence: 83%
“…Thus, R-carvedilol may be a safer and more effective alternative to carvedilol for preventing skin cancer. 24 Other researchers are exploring whether the mode of delivery of βblockers could offer an alternative oral carvedilol with fewer adverse effects for treating skin cancer. One study demonstrated that various doses of carvedilol packaged into transferosomes made of phospholipids and surfactants and delivered topically suppressed UVinduced DNA damage and inflammatory gene expression and promoted apoptosis.…”
Section: Interactionofβ-adrenergic Signalingwithimmunecellsmentioning
confidence: 99%
“…Female SKH-1 hairless mice, seven-eight week of age, were randomly divided into five groups (n = 5): (1) no UV negative control, (2) UV + acetone, (3) UV + 10 uM carvedilol in acetone (10 µM or 4 μg/mL, 0.8 μg per treatment), (4) UV + empty transfersomes gel formulation, and (5) UV + T-CAR gel formulation. The UV lamps used in these studies were described before (Liang et al, 2021). A half-hour prior to UV-radiation, the mice were pre-treated with different treatments as described above.…”
Section: Acute Uv Exposure Of Micementioning
confidence: 99%
“…Mice were pretreated with T-CAR and empty transfersomes three times a week for two weeks before starting UV exposure. The UV treatment protocol was described before (Liang et al, 2021). In brief, the mice were irradiated with gradually increasing levels of UV three times a week for 25 weeks with an initial dose of 50 mJ/cm 2 that was increased each week by 25 mJ/cm 2 to 150 mJ/cm 2 , which was continued for the duration of the experiment.…”
Section: Chronic Uv-induced Skin Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation